Pathogenic Escherichia coli in Dogs Reveals the Predominance of ST372 and the Human-Associated ST73 Extra-Intestinal Lineages - Valat, Charlotte; Drapeau, Antoine; Beurlet, Stéphanie; Bachy, Véronique; Boulouis, Henri-Jean; Pin, Raphaëlle; Cazeau, Géraldine; Madec, Jean-Yves; Haenni, Marisa (Frontiers in Microbiology, 2020)
Escherichia coli is a ubiquitous commensal and pathogen that has also been recognized as a multi-sectoral indicator of antimicrobial resistance (AMR). Given that latter focus, such as on resistances to extended-spectrum cephalosporins (ESC) and carbapenems, the reported population structure of E. coli is generally biased towards resistant isolates, with sequence type (ST)131 being widely reported in humans, and ST410 and ST648 being reported in animals. In this study, we characterized 618 non-duplicate E. coli isolates collected throughout France independently of their resistance phenotype. The B2 phylogroup was over-represented (79.6%) and positively associated with the presence of numerous virulence factors (VFs), including those defining the extra-intestinal pathogenic E. coli isolates (presence of ≥2 VFs: papA, sfaS, focG, afaD, iutA, kpsMTII) and those more specifically related to Uropathogenic E. coli (cnf1, hlyD). The major STs associated with clinical isolates from dogs were by far the dog-associated ST372 (20.7%) and ST73 (20.1%), a lineage that had commonly been considered until now as human-associated. Resistance to ESC was found in 33 isolates (5.3%), along with one carbapenemase-producing isolate, and was mostly restricted to non-B2 isolates. In conclusion, the presence of virulent E. coli lineages may be the issue, rather than the presence of ESC-resistant isolates, and the risk of transmission of such virulent isolates to humans needs to be further studied.